Implementasi Kebijakan TPS 3R Dalam Pengelolaan Sampah Daerah di Kota Bandar Lampung: Perspektif Siyasah Tanfidziyah - Wildan Kholid, Muhammad; Zuhraini; Ikhwani, Achmad (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the implementation of Regional Regulation of Bandar Lampung City Number 6 of 2023, Article 10 paragraph (2) letter b, concerning the provision of TPS 3R (Reduce, Reuse, Recycle waste management facilities), and to evaluate it from the perspective of Siyasah Tanfidziyah. The research employs an empirical juridical method with a qualitative approach. Data were collected through interviews, observations, and document analysis. The findings indicate that the implementation of the TPS 3R policy has not been optimal, primarily due to limited institutional capacity, low inter-actor integration, and weak community participation. These findings reveal a gap between policy norms and their practical implementation (implementation gap). From the perspective of Siyasah Tanfidziyah, this condition reflects the incomplete realization of the principles of public welfare (maslahah) and the effectiveness of executive authority in managing public affairs. This study contributes by offering an integrative approach that combines public policy analysis with the principles of Siyasah Tanfidziyah, and by emphasizing the importance of strengthening collaborative governance and promoting a circular economy as strategies to enhance the effectiveness of TPS 3R-based waste management policies